Greeks grapple with responsibility. Issue 10 (14th September 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings – Key findings denote occupational health and safety, benign environmental management as well as responsible production methods as the top corporate social responsibility (CSR) priorities. Two different CSR viewpoints emerged from the factor analysis reflecting a pragmatic and a more socially responsive interpretation of corporate responsibility. Cluster analysis confirmed such contrasting perspectives, allowing the partition of data in distinctive groups according to the relative inclination on either of the identified viewpoints. Similarity measures obtained from cluster analysis also verified the different CSR positions. Practical implications – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.